Overview of Oman Power Transmission System and Protection Schemes for Effective Energy Management in Smart Grid Operations - Al Omairi, Saif; Al Balushi, Marya; Okedu, Kenneth E. (Frontiers in Energy Research, 2021)
This paper presents an overview of the transmission system and protection schemes employed in the national power grid of Oman. The technical design requirements considering the percentage of allowable limits for the different transmission voltage levels in the power grid of Oman was considered, based on the electrical standards and grid codes of Oman. Also, the protection and fault requirements based on relay settings and back-up protection, were some of the factors considered in this study. More so, the power flow, peak and off-peak voltage profiles of the main interconnection and Dhofar transmission systems were analyzed in details, considering projections for 2021 and 2025, respectively, for effective energy management and smart grid operations. The current protection equipment of the power grid of Oman were evaluated and some improvement schemes were proposed considering the implementation of new technology for smart grid operation. The continuous investment in the transmission system of Oman power grid and the use of updated protection technology, would lead to the enhancement of the performance of Oman transmission system to reach a high level power transmission availability.